Avaliação de bacias de detenção de águas pluviais implantadas no município de São Carlos, SP - Rodríguez, Carlos Andrés Martínez (Universidade Federal de São Carlos, 2019)
In Brazil, the last decades registered an accelerated growth of urbanization, increasing the waterproofing of the soil and the direct flow, generating floods in the urban areas. As a measure to mitigate the resulting impacts, since the 90’s decade, the concept of compensatory techniques has been adopted, among them, the Detention Basins (DB), which are centralized techniques that are characterized by being dimensioned for large return periods, with the objective of detain rainwater over a period of time, reducing the flood peak. Due to the obligatoriness by the municipal legislation, DB are being implanted in new urban developments in the municipality of São Carlos, to guarantee the conservation of the pre-urbanization flow. According to this panorama, the present research has as objective the evaluation of these units under physical aspects, of project and urban integration. Were identified and characterized 23 Detention Basins and 3 Detention Basins Systems by satellite images and on-site visits, and were evaluated through variables consulted in the bibliographic review and adapted to the municipal reality. Also, aspects as sizing, construction, maintenance, costs and integration of some of the DB were analyzed through consultation of the memorials in the drainage projects and interviews with the agents involved with the issue. These resources permitted to identify that the location of the DB was directed to the perimeter zones of the municipality. Most of them being close to residences, but without being integrated in the same space of coexistence with the community, being isolated through gates and wiring. All DB have the sole function of hydrological control. The exception were three Basins that did not have a bottom hole for water outlet. The others DB presented shallow water sheet formation by the precipitation event and emptying it within 24 hours after rainfall. Regarding the state of conservation, it was observed as a common factor the presence of excessive vegetation and solid residues due to the lack of frequent maintenance activities. About sizing, was verified the use of the rational method to calculate the maximum flows. However, differences were identified in the calculation of hydrological parameters and the volume of detention in Basin’s drainage project, compared to the equations established by the Municipal Direction for Drainage Projects. Most DB had energy dissipators in their inlet structures preventing erosion, as well as elements for sediment retention. The activities necessary for the construction and operation of the DB do not represent a high complexity, being these mainly the soil movement and to prune along with the solid waste removal respectively. Two DB implantation cost ranges were identified, one of them at around R$25/ m³ and the other of R$50/m³; the calculated cost for the maintenance of the DB was R$342/ha.year. The DB implanted comply with the hydrological control function, but for a better integration of the technique in the urban environment it is necessary an improvement in the maintenance activities as well as the consideration of the multifunction of them in the conception of the urban project.
Evaluation of stormwater detention basins implanted in the municipality of São Carlos, SP
Keywords: Controle de cheias; Manejo de águas pluviais; Drenagem urbana; Técnicas compensatórias; Bacias de detenção; Flood control; Stormwater management; Urban drainage; Compensatory techniques; Detention basins; Control de inundaciones; Manejo de águas pluviales; Drenaje urbana; Técnicas compensatorias; Reservatorios de detención; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::CONTROLE DE ENCHENTES E DE BARRAGENS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::DRENAGEM URBANA DE AGUAS PLUVIAIS